Linking Strategic Orientation to Performance: Evidence of Competency-Mediated Effects in Emerging Market Student Entrepreneurs - Sam, Toong Hai; Mu’min, Halek; Sutrisno, Timotius. F.C.W.; Andrina, A. A. A. Puty; Hong, Heng Chin; Wahyudono, Denny Bernardus Kurnia (International Review of Management and Marketing, 2026)
This study examines how two strategic orientations—market orientation and sales orientation—affect business performance through the mediating role of entrepreneurial competencies within student-run micro and small enterprises. Grounded in the Resource-Based View (RBV), orientations are conceptualized as strategic capabilities that can enhance firm competitiveness when translated into individual-level entrepreneurial competencies. Using survey data collected from student entrepreneurs operating within a university-based entrepreneurship environment (n = 195) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results show that both market orientation and sales orientation exert significant positive effects on entrepreneurial competencies. Furthermore, entrepreneurial competencies demonstrate a strong and significant influence on business performance and mediate the relationship between both orientations and performance. These findings extend RBV theory by clarifying how strategic orientations yield performance benefits not directly, but through competency development at the individual level. Practically, the study highlights the importance of cultivating market-driven, sales-driven, social entrepreneurship and competency-focused training in entrepreneurship education to enhance the performance of student-run enterprises in emerging markets.